DETECTION OF BETA-DEFENSINS AND NOS IN HEALTHY AND PATHOLOGICAL NASAL MUCOSA - Pácová, Hana; Kučera, Tomáš; Astl, Jaromír; Martínek, Jindřich (Biomedical papers, 2004)
...
Keywords: Beta-defensin/Nitric oxide synthase/Apoptosis/Cell proliferation/Nasal polyposis